Leishmaniases as Re-emerging Diseases - Afrin, Farhat; Hemeg, Hassan (IntechOpen, 2018)
Leishmania parasites plague the mammalian host causing high morbidity and mortality. The parasites persist in the hostile milieu, crippling its defensive arsenal. In the face of mounting resistance to an antiquated drug arsenal, new approaches are urgently desired to keep the infection at bay. Furthermore, to strengthen the leishmaniasis elimination drive, particular emphasis has to be laid on identification of new targets and vaccination strategies. This book gives a brief glimpse of the epidemiology of leishmaniasis, immune evasion, vaccination, and therapeutic modalities that may work by untangling the immunological cross-wires of pathogenic cross-talk. The Conventional treatment and its drawbacks, the prospects of phytotherapy and nanomedicines, are also discussed. The identification of drug targets with the aim of designing inhibitors is also exemplified.